Gastro Intestinal Stromal Tumor : A Case Report (BIRDEM Medical Journal, 2013)
Gastro Intestinal Stromal Tumor (GIST) are a type of neoplasm arising from the embryological mesoderm of GastroIntestinal Tract. But they can also arise from extra intestinal sites. The incidence1 of site of origin of GIST is - Oesophagus 5% Stomach 50% Small intestine 25% Colon & rectum 10%, Extr-intestinal (Mesenchyme, GB,Pancreas) 10%.We present here a case of GIST attaining enormous size, having all classical histological features of GIST arising from the mesentery which is a relatively rare site. Birdem Med J 2013; 3(1): 47-49 DOI: http://dx.doi.org/10.3329/birdem.v3i1.17127